Development of Micro-scale Biomass-fuelled CHP System Using Stirling Engine - Ilva, Arashnia; G., Najafi; B., Ghobadian; Talal, Yusaf; R., Mamat; Maurice, Kettner (Elsevier Ltd, 2015)
In this research study, a Micro-scale Combined Heat and Power (MCHP) plant with a stirling engine for biomass fuels was developed and optimized. The nominal electric power output of the plant is 100 Watt. Currently this plant has run using wood powder as fuel. With consideration of the biomass energy potential, a gamma type Stirling engine with 220cc swept volume and 580cc total volume was designed, optimized and manufactured. The performance is investigated with regard to the operating conditions, the heat fluxes, temperatures and the type of biomass. Electrical energy produced from biomass sources. The results shows that the highest efficiency of the system is reached for moderate speed values of stirling engine approximately 500-600 rpm. Sugarcane bagasse, wood, wheat straw, poplar wood and sawdust as fuel system were selected. Most power be obtained from the sawdust (46 watt) and pruning of trees for wood for low power (21 watts), respectively. Minimum ignition time of the Sawdust (4 min) and the most time flammable wood from pruned trees (10 min) was measured. At maximum power, the internal thermal efficiency of the engine was measured as 16%. The test results confirm the fact that Stirling engines driven by temperature of biomass gases are able to achieve a valuable output power. Results of the present work encouraged initiating design of a MCHP system with 1 kWe capacity for rural electrification. So this operation can be considered as a breakthrough in the utilization of stirling engine for micro-scale CHP plants utilizing wood powder fuels.